PENGARUH KUALITAS KINERJA PELAYANAN PUBLIK TERHADAP KEPUASAN PENGUNJUNG PADA PERPUSTAKAAN BANK INDONESIA SUMATERA UTARA - Simanjuntak, Ester Yohana; Maharani, Hani Puspita; Sitanggang, Herikson Muksa Putra; Herlina Bernadecka Sidauruk; Effendi, Meilany Putri; Balqis, Nabila; Syafitri, Naisyah Qila; Naution, Nisa Ul Mahfuzha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the quality of public service performance on visitor satisfaction at the Bank Indonesia Library of North Sumatra. This research used a quantitative method with a survey approach involving 55 library visitors selected as respondents. Data were collected through questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS) through validity testing, reliability testing, descriptive statistical analysis, Pearson correlation, and simple linear regression. The results show that the quality of public service performance has a positive and significant effect on visitor satisfaction. The better the quality of service provided, the higher the level of satisfaction experienced by visitors. The findings also indicate that service quality plays an important role in improving library visitor satisfaction. Therefore, library management needs to continuously improve service quality, including facilities, service speed, and staff attitudes in serving visitors. This study is expected to serve as an evaluation tool and provide input for the Bank Indonesia Library of North Sumatra in efforts to improve service quality for the community.